Utilization of Tofu Dregs Flour in Processed Food Macaron as a Culinary Tourism Product in Banyuwangi Regency - Mumtaza, Nelin Nurul; Handoko, Rudi Tri; Nurhalimah, Nurhalimah; Joyo Widakdo, Danang Sudarso Widya Prakoso (JUPE : Jurnal Pendidikan Mandala, 2025)
The number of tofu industries in Banyuwangi certainly also produces its own waste which, if not properly processed, will pollute the environment. This research uses an R&D research approach with 4D development (Define, Design, Development, Dissemination) and is tested using the Organoleptic test (hedonic and hedonic quality) with 5%, 10%, and 15% tofu dregs flour substitutions that pay attention to aspects of aroma, taste, texture, and color. The purpose of this research is useful to increase knowledge about innovation in processing tofu pulp and to know the process of making Macarons with tofu pulp flour substitution. In the hedonic quality organoleptic test that has been carried out to 5 trained panelists, the best tofu dregs flour substitution is 10%, while for the hedonic organoleptic test to 15 semi trained panelists, the result is 86% where the value is included in the very like category.